2011
DOI: 10.1111/j.1365-2745.2011.01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Distance to stable stage distribution in plant populations and implications for near-term population projections

Abstract: Summary1. Matrix population models capture how variation in vital rates among life stages translates to population dynamics. Analyses of these models generally assume that populations have reached a stable stage distribution (SSD), where the proportion of individuals in each stage remains constant. However, when life stages respond differentially to environmental cues and perturbations, a population may be moved away from equilibrium. Given the multitude of stochastic processes acting in natural systems, popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 35 publications
2
52
2
Order By: Relevance
“…Combining several recently published databases of perennial plant models (Stott et al 2010, Crone et al 2011, Williams et al 2011, Ellis et al 2012 we identified 25 populations from nine species (Appendix) for which annual transition matrices had been constructed from annual population surveys, and for which ''white noise'' stochastic models seemed appropriate. In other words, variation among years was not due to succession after disturbance, or periodic drivers such as fire cycles.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining several recently published databases of perennial plant models (Stott et al 2010, Crone et al 2011, Williams et al 2011, Ellis et al 2012 we identified 25 populations from nine species (Appendix) for which annual transition matrices had been constructed from annual population surveys, and for which ''white noise'' stochastic models seemed appropriate. In other words, variation among years was not due to succession after disturbance, or periodic drivers such as fire cycles.…”
Section: Study Speciesmentioning
confidence: 99%
“…How frequently this assumption is adequately met is unclear (Bierzychudek 1999, Williams et al 2011, as are the implications of deviances from SSD in model applications (Ezard et al 2010, Johnson et al 2010. Consequently, there has been an increasing focus on analyzing the short-term, transient dynamics that result when populations are not at SSD (e.g., Fox and Gurevitch 2000, Caswell 2007, Stott et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an episodic reproductive outburst after the ENSO, when drought conditions ended, could explain the observed seedling overabundance. Episodic recruitment events have been reported to produce population models where SSD is different from current observations [14,45,49]. As ENSO-related droughts are likely to become more frequent and severe due to global warming [48], the consequences of such climatic change on long-lived plant fitness and sustainable management of NTFPs should be urgently assessed.…”
Section: The Matrix Model: Enso Related Transient Dynamics?mentioning
confidence: 99%
“…Transient dynamics can be strong when populations are moved away from their SSD following an unusual disturbance [14,45]. The 1997-98 El Niño Southern Oscilation (ENSO) was one of the strongest ever recorded [46], causing a water shortage and high temperatures at La Planada, and a pause in flowering bud production for P. acuminata [9].…”
Section: The Matrix Model: Enso Related Transient Dynamics?mentioning
confidence: 99%
See 1 more Smart Citation